Kajian Pelaksanaan Program Kartu Prakerja dalam Meningkatkan Kesejahteraan Keluarga di Kabupaten Badung - Indra Yanti, Ni Komang Ayu; Punia, I Nengah; Sastri Mahadewi, Ni Made Anggita (JURNAL ILMIAH SOSIOLOGI (SOROT), 2021)
Indonesia is a developing country with various problems in it, one of which is unemployment. The cause of unemployment in Indonesia is due to the low quality of the workforce. One way from the government to improve the quality of the workforce is by issuing the Pre-Employment Card Program. The Pre-Employment Card program can help the community improve family welfare (fulfillment of needs). As a form of empowerment program for the community, only 4 concepts of empowerment have been implemented, namely the existence of resources, opportunities, knowledge or education, and training. Meanwhile, sustainable empowerment and the role of a companion does not exist, because incentives can only be used to meet daily needs and are not sufficient for business capital. In addition, there is no form of evaluation as the end of an empowerment program to determine the level of success of the program in the Pre-Employment Card Program. Keywords: Pre-Employment Card Program, Family Welfare, Community Empowerment, Implementation, Impact.